Genome‐Wide Identification of DNase I Hypersensitive Sites in Plants. Issue 6 (8th June 2021) - Wang, Yankun; Wang, Kai
Abstract: DNase I hypersensitive site (DHS) mapping combined with high‐throughput sequencing (DNase‐seq) enables the identification of cis ‐regulatory DNA elements (CREs) genome wide. However, despite the wide applications of DNase‐seq in plants, its application to the highly repetitive genomes of plants has lagged. Here, we describe a modified DNase‐seq method, making it more practical for application to plants with genomes enriched with repetitive DNA. This approach adopts a double‐hit‐based strategy, in which small (<250‐bp) DNA fragments digested by DNase I are selected and used for sequencing library construction. Using these protocols, we have conducted DNase‐seq in plants with high content of repetitive DNA, including maize, sugarcane, and tetraploid cotton. Genome‐wide maps of DHS and CREs have been created using these DNase‐seq datasets. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Nuclei isolation Basic Protocol 2 : DNase I digestion Basic Protocol 3 : Target DNA isolation Basic Protocol 4 : Library construction and validation